Glucagonoma-associated necrolytic migratory erythema: the broad spectrum of the clinical and histopathological findings and clues to the diagnosis - Toberer, Ferdinand; Hartschuh, Wolfgang; Wiedemeyer, Katharina (The American journal of dermatopathology, 2019)
Necrolytic migratory erythema (NEM) is associated with glucagonoma, an endocrine malignancy of the pancreas. It is a rare and a likely underrecognized paraneoplastic dermatitis. A 38-year-old woman presented to our clinic with a 3-year history of reocurring pruritic skin rashes with increasing intensity. The skin lesions presented with active annular borders, central scaling, and postinflammatory hyperpigmentation, but also with erosions, pustules, and crusted lesions. Multiple skin biopsies were taken. The workup of the patient revealed a tumor localized in the head of the pancreas, and glucagon serum levels were elevated. Clues to the diagnosis of NEM were the waxing and waning of serpiginous erythemas with active borders localized on extremities, intertriginous areas, and face. On histopathology, dyskeratosis in all layers of the epidermis were an early feature of NEM, and long-standing lesions typically showed psoriasiform hyperplasia with pallor and necrosis of upper epidermal layers. Clinicians and histopathologists need to be aware of the wide spectrum of skin manifestations in glucagonoma. Early diagnosis of the tumor is crucial for patients.
Gesehen am 13.06.2019